Implementasi Ultimum Remedium Berdasarkan Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup di Sumatera Utara - Herman Brahmana; Marthin Richardo Marpaung; Ridho Try Horas Tampubolon; TriIvama Melati Hutabarat; Edward Arifsandi Tarigan (CV Rewang Rencang, 2025)
This study examines the application of the Ultimum Remedium principle in addressing forest degradation based on Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH). This principle positions criminal law as a last resort after administrative and civil efforts have been exhausted. Using a normative juridical method, the study finds that although the principle is explicitly regulated in the UU PPLH, its implementation remains ineffective due to weak oversight and lack of inter-agency coordination. The study emphasizes the importance of clarifying the limits of criminal law enforcement to ensure that perpetrators are not exempt from legal accountability. It recommends strengthening administrative law enforcement and cross-sector coordination to support justice and sustainability in environmental legal policy.